Dialog antara Amsal 17:17 dan Siri’ na Pacce: Eksplorasi Nilai Kebijaksanaan - Agustinus Abraham (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2025)
This article explores the dialogue between Proverbs 17:17, a part of biblical Wisdom Literature, and Siri’ na Pacce, a traditional value system of the Bugis-Makassar ethnic group. Both emphasize universal values such as love, solidarity, empathy, and human dignity within community life. Proverbs 17:17 underscores the importance of a faithful and loving friend especially in difficult times, while Siri’ na Pacce highlights honor (siri’) and compassion in suffering (pacce). This study employs a qualitative approach through literature review to analyze scriptural texts and local philosophies contextually. The findings indicate that these two traditions complement each other and enrich Christian faith expression in local cultural contexts. Their integration also supports the development of contextual theology and contributes to building a compassionate and dignified society. In an increasingly individualistic world, these values remain relevant in strengthening relationships and fostering inclusive communities of faithAbstrakArtikel ini mengeksplorasi dialog antara Amsal 17:17 sebagai bagian dari Sastra Kebijaksanaan dalam Alkitab dan falsafah hidup siri’ na pacce sebagai kearifan lokal Bugis-Makassar. Keduanya menekankan nilai-nilai universal berupa kasih, solidaritas, empati, dan martabat dalam kehidupan bermasyarakat. Amsal 17:17 menegaskan pentingnya kesetiaan dan kasih seorang sahabat terutama dalam masa sulit, sementara siri’ na pacce menyoroti pentingnya harga diri (siri’) dan solidaritas dalam penderitaan (pacce). Penelitian ini menggunakan pendekatan kualitatif melalui studi pustaka untuk menganalisis teks-teks kitab suci dan filosofi lokal secara kontekstual. Hasil analisis menunjukkan bahwa nilai-nilai tersebut saling melengkapi dan mampu memperkaya pemahaman iman Kristen dalam konteks budaya lokal. Integrasi keduanya juga menjadi dasar pengembangan teologi kontekstual dan membangun masyarakat yang bermartabat dan penuh kasih. Dalam dunia yang cenderung individualistik, nilai-nilai ini tetap relevan untuk memperkuat relasi dan membentuk komunitas iman yang inklusif.